Cholesterol remnants and triglycerides are associated with decreased myocardial function in patients with type 2 diabetes. Issue 1 (December 2016) - Jørgensen, Peter; Jensen, Magnus; Biering-Sørensen, Tor; Mogelvang, Rasmus; Galatius, Søren; Fritz-Hansen, Thomas; Rossing, Peter; Vilsbøll, Tina; Jensen, Jan
Abstract Background Recently, genetic studies have suggested a causal relationship between cholesterol remnants and ischemic heart disease. We aimed to determine whether cholesterol remnants and its marker, triglyceride levels, are associated with cardiac function as determined by sensitive echocardiographic measures in a population of patients with type 2 diabetes. Methods Comprehensive echocardiography including 2D-speckle tracking echocardiography was performed on a representative sample of 924 patients with type 2 diabetes—730 of whom were treated with statins. These were recruited from two large secondary care centers. Results In multivariable analyses, triglycerides and cholesterol remnants were not associated with left ventricular ejection fraction, but with subtle measures of systolic function, including global longitudinal strain by speckle tracking and longitudinal displacement by tissue Doppler echocardiography: global longitudinal strain [0.33 % (0.14), p = 0.02 per doubling in cholesterol remnants and 0.28 % (0.13), p = 0.03 per doubling in triglyceride levels] and with longitudinal displacement [−0.25 mm (0.10), p = 0.01 per doubling in cholesterol remnants and −0.25 mm (0.09), p = 0.005 per doubling in triglyceride levels]. Subgroup analyses of patients receiving statin therapy and patients without known heart disease revealed similar results, but the association was not present in patients with known heart disease. Conclusion In patients with type 2 diabetes, subtle decrease in left ventricular function is present with increasing levels of cholesterol remnants and triglyceride levels indicating an effect of these on cardiac function that is not detectable by conventional echocardiography.